Determinants of time limit at velocity corresponding to VO2max in physically active individuals - Jefferson da Silva Novaes; Jorge Roberto Perrout de Lima; Tony Meireles dos Santos; Leonardo Gonçalves Ribeiro (Universidade Federal de Santa Catarina, 2008)
The objective of the present study was to determine the relationship between time limit (Tlim) at VO2Máx velocity (VVO2Máx) and the variables VO2Máx, VVO2Máx, running economy (RE), ventilatory threshold (VT), strength test (9-10 maximum repetitions), velocity at maximal anaerobic running test (VMART), vertical jump test and body fat percentage. The sample was composed of 18 male volunteers, aged between 18 and 45 years old, non-athletes, but physically active. The study was carried out during fi ve visits, on non-consecutive days and at approximately the same time each day: visit 1 - signature of informed consent form, medical history, anthropometric assessment, aerobic power test and familiarization with Tlim test; visit 2 - RE test and Tlim test; visit 3 - familiarization with VMART test; visit 4 - familiarization with vertical jump and 9-10 maximum repetition tests and VMART test; visit 5 - vertical jump and 9-10 maximum repetition tests. Low (r = 0.220 to - 0.359) and non-significant correlations (p = 0.281 to 0.935) were observed between Tlim and the selected variables, characterizing the low predictive value of Tlim for the sample studied. Thus, and because of the considerable inter-individual variability in Tlim, no variable was identified that was capable of satisfactorily predicting Tlim. Resumo O objetivo do presente estudo foi determinar a relação do tempo limite (Tlim) na velocidade do VO2Máx (VVO2Máx) com as variáveis VO2Máx, VVO2Máx, economia de corrida (EC), limiar ventilatório (LV), força isotônica (determinada pelo teste de 9-10 RM), velocidade no teste máximo de corrida anaeróbica (VMART), impulsão vertical e percentual de gordura (%G) . A amostra foi composta por 18 voluntários do sexo masculino, com idade entre 18 e 45 anos, não atletas, regularmente ativos. O estudo foi realizado em cinco visitas, em dias não consecutivos e aproximadamente no mesmo horário, compostas de: visita 1 - assinatura do termo de consentimento, anamnese, avaliação antropométrica, teste de potência aeróbia e familiarização ao teste de Tlim; visita 2 - teste de EC e teste de Tlim; visita 3 - familiarização ao teste de VMART; visita 4 - familiarização aos testes de impulsão vertical e 9-10 RM e teste de VMART; visita 5 - testes de impulsão vertical e 9-10 RM. Foram observadas correlações baixas (r = 0,220 a - 0,359) e não significativas (p = 0,281 a 0,935) entre Tlim e as diversas variáveis selecionadas, o que caracteriza uma baixa qualidade preditiva para o TLim na amostra estudada. Neste sentido e tendo em vista a considerável variabilidade inter-indivíduos do TLim, não foi encontrada uma variável que pudesse predizê-lo satisfatoriamente.